Estudo etnofarmacológico sobre Lafoensia replicata Pohl. no leste do Maranhão, Brasil: uma promissora espécie para bioprospecção - Francisco Chagas Bila Sobrinho; Alyson Luiz Santos Almeida; Julio Marcelino Monteiro (Desenvolvimento e Meio Ambiente, 2016)
This work aimed at carrying out a study on the local therapeutic uses of mangabeira (Lafoensia replicata Pohl.), an important plant in the northeastern cerrado. 32 interviews were conducted with informants from the community Manga, Barão do Grajaú, Maranhão. Respondents, 18 women and 14 men, reported eight different uses for the plant. Regarding the number of instructions for use, there were no significant differences between genders, eight nominations described by women and seven by men. Regarding the distinctions of knowledge among the age group proposed for the analysis, there were no statistical differences. The plant part most indicated for use was the stem bark. All informants indicated consensually that the medicine prepared from the plant should be administered orally and over half of the respondents mentioned that the plant had no restrictions on consumption (53%). However, 17 respondents said that the treatment is contraindicated during pregnancy, and even five people did not recommend the use on children. It was not possible to substantiate the ethno-pharmacological information in this study with the literature since there is insufficient research on this species. There is some research focusing on uses and activities of Lafoensia pacari A. St.-Hil, therefore, this study also recommends L. replicata Pohl. as a potential therapeutic species.